Training In Preparing Financial Statements with Simple Booking Techniques in Group Farmers Batang Sirih Dusun Lubuk Rattan I, Desa Teluk, Kecamatan Secanggang, Kabupaten Langkat - Rangkuti, May Hana Bilqis; Kesuma, Sambas Ade; Risanty; Agustrisna, Juwita (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2022)
Batang Sirih Farmers Group is a farming group located in Teluk Village, Secanggang District, Langkat Regency, North Sumatra Province. This farmer group has approximately 30 members. The purpose of establishing the Batang Sirih farmer group is to empower farmers to gain skills and experience in the hope that later they can generate income and improve their economy. In its development, the Batang Sirih Farmer Group has now carried out a variety of Micro, Small and Medium Enterprises (MSMEs) as a livelihood related to farming management, including herbal business, plant fertilizer business, and other agricultural crops. However, in carrying out its business, the Batang Sirih Farmers Group encountered several problems related to its business. The main problem that is often faced by business actors is the lack of awareness to record business finances because of the lack of knowledge about financial accounting, resulting in the business financial system being unable to distinguish between business profits and household finances. This activity aims to provide a guide that can be used by every MSME to make financial reports.